How Do the Socio-economic Characteristics of Individual Members Influence the Business Effectiveness and Performance of Self-help Groups with Concerning Sustainable Development Goals: An SEM Approach - Verma, Priyanka; Raghuwanshi, Sandeep; Mishra, Ekta; Mishra, Apoorwa; Khare, Vikas Kumar (International Journal of Economics and Financial Issues, 2024)
This study investigates how the socio-economic characteristics of individual members influence the business effectiveness and performance of Self-Help Groups (SHGs) in the context of sustainable development goals, with a focus on the cities of Bhopal, Indore, Gwalior, and Jabalpur in Madhya Pradesh. The research is underpinned by the sustainable development goals framework, emphasizing the role of social capital and economic empowerment in the success of SHGs. Data were gathered from 384 SHG members using a standardized questionnaire. Structural Equation Modeling (SEM) was employed through SmartPLS to analyze the impact of various socio-economic factors, including income level, social capital, educational attainment, household size, and age of the respondents on SHG performance. The analysis reveals that household size and age do not significantly impact SHG performance. However, income level, social capital, and educational attainment are significant contributors to the effectiveness and performance of SHGs. The findings underscore the importance of these variables in achieving the sustainable development goals through SHG initiatives. The study provides actionable insights for policymakers and SHG organizers, suggesting that targeted interventions should focus on enhancing income levels, social capital, and education among SHG members to improve group performance and support sustainable development. This research adds to the literature by offering a region-specific analysis of the socio-economic factors influencing SHG performance, with empirical evidence from key cities in Madhya Pradesh, contributing to the broader discourse on sustainable development.